The constraints and concerns regarding the size and/or shape of the second generation female condom: The narratives from the healthcare providers - Ramadimetja Mogale; Fhumulani M. Mulaudzi; Mmapheko D. Peu; Mamakwa S. Mataboge; Roinah Ngunyulu; Salaminah S. Phiri (AOSIS, 2016)
Background: Despite the redesigning of the Reality condom (FC) to a new version of the second generation female condom commonly known as (FC2), the users are persistently constrained and concerned about the size and shape of this new version. Condom use is aligned to the Millennium Development Goals (MDG) 3, 5 and 6, which address gender equality, improving maternal health and preventing HIV and AIDS. Aim: To explore and describe the constraints and concerns regarding the size and/or shape of the FC2. Setting: The study was conducted at Tshwane health district in Gauteng province. Methods: A qualitative exploratory descriptive design was used. Individual in-depth interviews that yielded narratives in a designated health district in South Africa were conducted. Results: From the analysis of narratives three specific themes emerged. Firstly, the specific theme was that the size and shape of FC2 is undesirable for the health care providers, which may lead women to contract HIV and AIDS. The second theme was that the size and shape of FC2 and female genitals makes insertion complicated and predisposes women to be vulnerable in sexual relationships. The third was that the size and shape of FC2 results in pain and discomfort during coitus, exposing women to unwanted pregnancies and HIV and AIDS. Conclusions: The findings indicated the need for an evocative collaborative, interdisciplinary 'walk the talk' sexual health and AIDS education training programme for health care providers in primary health care facilities. Such programmes, if maintained, may assist health care providers to achieve the MDG 3, 5 and 6.